2013
DOI: 10.1111/fog.12035
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of larval fish self‐recruitment in a marine protected area

Abstract: The factors that regulate the self‐recruitment of fish larvae were explored in Cabrera National Park (CNP), an insular Marine Protected Area (MPA) located off southern Mallorca (Western Mediterranean). Our study attributes the regulation of larval arrival to the MPA to a combination of retention by topographically generated circulation patterns around the island and shelf break frontal dynamics. Specifically, within the shelf, interaction of the wind‐induced oscillatory flow with the island was shown to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Consequently, the scenarios with these winds had the greatest recruitment potential. Other studies have similarly found that wind induced oscillatory flow patterns can concentrate plumes of fish larvae, facilitating recruitment (Basterretxea et al, 2013). Further, the winds identified to be favorable for recruitment in this study were highly seasonal.…”
Section: The Wind and Recruitmentsupporting
confidence: 69%
See 1 more Smart Citation
“…Consequently, the scenarios with these winds had the greatest recruitment potential. Other studies have similarly found that wind induced oscillatory flow patterns can concentrate plumes of fish larvae, facilitating recruitment (Basterretxea et al, 2013). Further, the winds identified to be favorable for recruitment in this study were highly seasonal.…”
Section: The Wind and Recruitmentsupporting
confidence: 69%
“…When they were programmed to swim the upper limit of the modeled rate of return increased significantly, with the projected rates ranging from 0.4 to 28.8%. Many studies have similarly found that the inclusion of behavior in models vastly improved the predicted larval retention and subsequent recruitment (e.g., Paris et al, 2007;Butler et al, 2011;Basterretxea et al, 2013). In addition to improving the overall projected recruitment, when larvae were made to swim, they counteracted the adverse dispersive forces of strong winds and the CE.…”
Section: The Importance Of Larval Swimming Behaviormentioning
confidence: 99%
“…When no data is available, the bias associated with their absence could be estimated by comparing dispersal patterns obtained from passive simulations and from simulations of caricatured behaviors (e.g., swimming at high speed and perfectly oriented), as part of a sensitivity study. North et al (2009) provide suggestions for the implementation of such sensitivity approaches and Basterretxea et al (2013) is an example of such a study in the Mediterranean.…”
Section: Toward More Accurate Connectivity Models In the Mediterraneamentioning
confidence: 99%
“…Overall, we interpret the predicted patterns of connectivity at scales of tens to hundreds of kilometers, for which the resolution of 1.2 km is not limiting. In contrast, to answer similar questions (regional connectivity and rates of larval retention), other studies used much lower resolutions (e.g., >12 km; Andrello et al, , 2015) or integration time steps allowing larvae to cross more than one grid cell in a single step (Basterretxea et al, 2013). Such use of unsuitable configurations could skew the dispersal patterns obtained (North et al, 2009).…”
Section: Toward More Accurate Connectivity Models In the Mediterraneamentioning
confidence: 99%
See 1 more Smart Citation